(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article provides data on the influence of the degree and type of salinization of meadow soils of the Bukhara oasis on the content and supply of humus, as well as nutrients. It is noted thatsoda salinization and increased sodium content, increasing the concentration of soil solution and pH of the medium, worsens the formation of humus and nutrients.